Wave spectral finite element model for the prediction of sound transmission loss and damping of sandwich panels. (1st October 2015) - Mejdi, Abderrazak; Atalla, Noureddine; Ghinet, Sebastian
Highlights: WSFEM based approach is developed for vibro-acoustic analysis of sandwich panels. Sandwich with skin and core fabricated from various layers can be analyzed. The model accuracy is analyzed by comparison with numerical models and experimental data. The present model accurately reproduced the STL and DLF of various sandwich structures. The present model is found quick and accurate. Abstract: Sandwich panels are usually modeled by considering only asymmetric motion which assumes the core deforms by transversal shearing without any compressive deformation over the thickness. This assumption is acceptable for panels with relatively stiff and thin cores. However, symmetric motion becomes important when the core is thick or soft. Under such conditions, the compressive deformation over the core thickness becomes significant. This paper addresses the prediction of the Sound Transmission Loss (STL) and composite Damping Loss Factor (DLF) of sandwich panels with either thin or thick cores as well as stiff or soft (viscoelastic) cores. Both the skin and the core are assumed to be orthotropic. A spectral finite element based approach is developed wherein the stress and strain components in each layer are described using the properties in that layer for a forced trace wave number and heading direction. The proposed approach provides a reliable and numerically efficient tool to account for the compressive deformation effect of thick orthotropic sandwich layers. Moreover, the proposed model is also able to consider panels with multiple of layers with varying properties.